Pobreza multidimensional nos estados brasileiros de 2003 a 2015 : mensuração e determinantes - Ferreira, Taís Regina da Silva (2018)
The purpose of this research is to verify the impact of economic and social variables on poverty, measured from the Multidimensional Poverty Index (MPI) of the Brazilian states, calculated for the period from 2003 to 2015. The index was developed using the Alkire- Foster method and made use of data from the National Household Sample Survey (PNAD). To achieve the study goal, we applied the econometric methodology of panel data - fixed effects, where the MPI was the dependent variable and we test the relation with the participation rate in the economy, the growth rate, the per capita household income, direct government transfers per capita, municipal social public expenditures per capita, and state public expenditures per capita. The results indicate that policies aimed at the distribution of direct income, such as the Bolsa Família Program, are more effective in reducing multidimensional poverty, compared to municipal and state public expenditures. On the other hand, even with less impact, municipal and state public expenditures also reduce poverty. The states of the North and Northeast presented the highest MPIs and the indicator "did not have any type of contribution with the social security" was the one that the individuals presented greater deficiency within the analyzed period.